Association between Kniest dysplasia and chondrosarcoma in a child. (8th September 2015) - Hochart, Audrey; Dieux, Anne; Coucke, Paul; Fron, Damien; Fayoux, Pierre; Labalette, Pierre; Boutry, Nathalie; Escande, Fabienne; Aubert, Sébastien; Renaud, Florence; Rocourt, Nathalie; Vinchon, Matthieu; et al.
Abstract : Constitutive COL2A1 mutations are associated with a wide variety of clinical manifestations known as type II collagenopathies. Among them is Kniest dysplasia, which is phenotypically variable and includes both skeletal (short trunk and limbs, kyphoscoliosis, prominent joints, and osteoarthritis) and craniofacial characteristics. Kniest dysplasia mutations primarily arise in the triple‐helicoidal region of the alpha 1 (II) chain in COL2A1 between exons 12 and 24. Somatic COL2A1 mutations have been identified in chondrosarcoma, a rare cartilage forming neoplasm, with a hypermutability of the gene reported in 37% of cases. However, to the best of our knowledge, there is no reported increase in predisposition to chondrosarcoma in human collagenopathies, and no reported clinical association between these congenital diseases and cartilaginous tumors. In the case study presented here, we report the first description of an association between these two rare diseases involving COL2A1, in a child presenting with Kniest dysplasia and a grade I sphenoethmoidal chondrosarcoma. We also describe a new constitutive mutation in COL2A1 . © 2015 Wiley Periodicals, Inc.